Consumer behavior towards on-net/off-net price differentiation - Justus Haucap; Ulrich Heimeshoff (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
This paper explores how consumers react towards price differentiation between on-net and off-net calls in mobile telecommunications - a pricing policy that is common in many mobile telecommunications markets. Based on a survey of 1044 students we demonstrate that some consumers may suffer from a 'price differentiation bias', i.e., a fair number of consumers may overestimate the savings that result from reduced on-net and/or off-net charges, as they do not appear to weigh the prices with the probabilities of placing off-net and on-net calls. This may help to explain why it have been the smaller operators in various countries who have introduced on-net/off-net price differentiation. We also discuss the implications that such a consumer bias may have for market competition.
Keywords: L40; L96; 330